2006
DOI: 10.1086/503351
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Stability and Habitability of the γ Cephei Binary‐Planetary System

Abstract: It has been suggested that the long-lived residual radial velocity variations observed in the precision radial velocity measurements of the primary of Cephei ( HR 8974, HD 222404, HIP 116727) are likely due to a Jupiterlike planet orbiting this star. In this paper, the dynamics of this planet is studied, and the possibility of the existence of a terrestrial planet around its central star is discussed. Simulations, which have been carried out for different values of the eccentricity and semimajor axis of the b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 47 publications
5
69
0
Order By: Relevance
“…We assumed an edge-on configuration. This is an important restriction, since any inclination of the orbital plane of the binary would lead to much higher values of m B (see Hatzes et al 2003;Haghighipour 2006). Although both fits correspond to significantly different dynamical systems, they yield practically the same residuals: (χ 2 ν ) 1/2 = 1.98.…”
Section: Possible Orbital Solutions For γ-Cepheimentioning
confidence: 96%
See 1 more Smart Citation
“…We assumed an edge-on configuration. This is an important restriction, since any inclination of the orbital plane of the binary would lead to much higher values of m B (see Hatzes et al 2003;Haghighipour 2006). Although both fits correspond to significantly different dynamical systems, they yield practically the same residuals: (χ 2 ν ) 1/2 = 1.98.…”
Section: Possible Orbital Solutions For γ-Cepheimentioning
confidence: 96%
“…It is then no surprise that this planetary system has caught the attention of several researchers over the past decade, and many dynamical and collisional studies may be found in the literature (e.g. Thébault et al 2004Thébault et al , 2006Haghighipour 2006;Verrier & Evans 2006;Tsukamoto & Makino 2007;Paardekooper et al 2008;Xie & Zhou 2008;Kley & Nelson 2008;Paardekooper & Leinhardt 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have studied planet formation and migration in the γ Cephei system (Dvorak et al 2004;Thébault et al 2004;Haghighipour 2006;Verrier & Evans 2006;Kley & Nelson 2008;Jang-Condell et al 2008;Paardekooper et al 2008;Xie & Zhou 2008;Paardekooper & Leinhardt 2010). We also consider the parameters of this binary (values taken from Torres 2007) as a starting point in our study.…”
Section: Introductionmentioning
confidence: 99%
“…Among the currently known extrasolar planet-hosting stars, approximately 20% are members of binaries or multiple systems (Haghighipour 2006). Nearly all of the planets in these systems revolve around only one of the stars.…”
Section: Introductionmentioning
confidence: 99%